Exploring the Role of Social Media in Disaster Management: A Case Study of the 2021 South Kalimantan Flood - Hidayat, Muhammad Nizar; Fahrianoor; Siswanto (CHANNEL: Jurnal Komunikasi, 2024)
The emergence of social media has opened huge potentials for the risk mitigation in disaster management. However, the big flood in 2021 that swept almost entire South Kalimantan territory has left some questions about the relations of social media and risk mitigation despite the prevalence of social media users in the region. This article sought to describe the utilization (or lack thereof) of social media in the disaster management in the South Kalimantan especially in Banjar Regency, Hulu Sungai Tengah Regency, and Tabalong Regency before, during and after the big flood. The data are gathered by conducting systematic interviews with stakeholders, observation, and collecting related information from the internet. For the result, it was evident that social media platforms like Facebook, WhatsApp, and Instagram played critical roles where traditional communication systems failed or were nonexistent. In Banjar, external volunteers utilized these platforms to coordinate aid and disseminate crucial information, in contrast, the initial disregard for digital communications in HST highlighted the challenges of media literacy and trust in digital platforms, while the case of Tabalong serves as a model for other regions, demonstrating how leveraging local knowledge and social media can create a resilient and responsive community.